The problems of professionals - Saariluoma, Pertti (Human Technology, 2008)
hen we discuss interaction and communication technology (ICT) usability, the images of ordinary users facing difficulties in getting things to work come easily to mind. People who struggle to use digital applications or find mobile services, or feel lost or frustrated when trying to use all of the features of a remote controller seem to form the very stereotype of users that interaction research should help. How my auntie, elderly neighbor, or disabled brother could survive in an ICT-infused world is a recognized problem today, although not that long ago, their problems were not a priority. The main focus of the research had been on early middle-aged families with Western backgrounds (Czaja, 1997; Newell & Gregor, 1997).